THE INFLUENCE OF NOTICE OF TAX COLLECTION AND NOTICE OF TAX UNDERPAYMENT ASSESSMENT ON REVENUE OF INCOME TAX ARTICLE 25 (STUDY AT TAX OFFICE MADYA MALANG PERIOD OF 2009 – 2013) - Faizah, Ni'matul (Jurnal Mahasiswa Perpajakan, 2014)
Self Assessment System that is used in Indonesia obliges all taxpayers to have active participation in fulfilling their tax obligation. However, during these times there are a lot of mistakes or errors that done by taxpayers in reporting their taxes. Government through Directorate General of Taxes (DGT) conducts tax verification and tax audit in the form of corrective action as well as law enforcement in taxation sector. These actions generate Notice of Tax Collection and Notice of Tax Underpayment Assessment. Problem of this research is do variable of Notice of Tax Collection (LnX1) and Notice of Tax Underpayment Assessment (LnX2) have significant influence on revenue of Income Tax Article 25 (LnY) both simultaneously and partially. Type of research that is used is explanatory research. The result of F-Test shows that LnX1 and LnX2 have significant influence on LnY simultaneously. Meanwhile, t-Test results negative insignificant influence for LnX1 toward LnY and positive significant result for LnX2 on LnY. Keywords: tax verification, tax audit, Notice of Tax Collection, Notice of Tax Underpayment Assessment, tax revenue